2002
DOI: 10.1159/000069715
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide: Increased Concentrations in Homemade Food and First Evidence of Its Variable Absorption from Food, Variable Metabolism and Placental and Breast Milk Transfer in Humans

Abstract: We have developed a liquid chromatography/mass spectrometry (LC-MS/MS) assay to determine acrylamide in various body fluids. The assay also allows the reliable quantitation of acrylamide in food. In a total of 11 healthy male and female subjects, we were able to show that acrylamide from food given to humans is in fact absorbed from the gut. The half-lives determined in two male subjects were 2.2 and 7 h. Acrylamide was found in human breast milk and penetrated the human placenta (n = 3). The variability of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
5
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 28 publications
5
110
5
4
Order By: Relevance
“…This suggests that the AA levels in the different foods, published by Svensson et al (2003), should approximately be similar to the AA levels in foods during 1990s, when the MDC cohort was established. Data for AA in home cooked foods are not available, which particularly is a limitation as a feeding study indicated that the AA content in home cooked foods could be much higher than in similar commercial products (Sörgel et al, 2002). Moreover, the AA content may vary between for example, different brands of the same food, suggesting that the true dietary variation may be underestimated (by studies like ours) when only one published source is used to estimate intakes.…”
Section: Factors Contributing To Weak Associationsmentioning
confidence: 80%
“…This suggests that the AA levels in the different foods, published by Svensson et al (2003), should approximately be similar to the AA levels in foods during 1990s, when the MDC cohort was established. Data for AA in home cooked foods are not available, which particularly is a limitation as a feeding study indicated that the AA content in home cooked foods could be much higher than in similar commercial products (Sörgel et al, 2002). Moreover, the AA content may vary between for example, different brands of the same food, suggesting that the true dietary variation may be underestimated (by studies like ours) when only one published source is used to estimate intakes.…”
Section: Factors Contributing To Weak Associationsmentioning
confidence: 80%
“…Hb adducts accumulate over the life span of the erythrocytes and during chronic exposure the adduct level reflects the average exposure/internal dose during the last months. Other measures of exposure of AA, so far rarely used, are mercapturic acids in urine, or free AA in plasma and urine, reflecting the exposure during the last days [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Glycidamide was found to pass through placenta and distributed in fetal tissues and also pass through mother's milk during lactation [31] . Abou-Donia et al [32] reported that brain stem of glycimide-treated rats exhibited axonal degeneration with chromatolytic necrosis in midbrain medial and lateral reticular nuclei.…”
Section: Discussionmentioning
confidence: 99%